Athenian potters and painters, - Oakley, John Howard, 1949- (Oxbow Books, 2014)
Athenian Potters and Painters III presents a rich mass of new material on Greek vases, including finds from excavations at the Kerameikos in Athens and Despotiko in the Cyclades. Some contributions focus on painters or workshops - Paseas, the Robinson Group, and the structure of the figured pottery industry in Athens; others on vase forms - plates, phialai, cups, and the change in shapes at the end of the sixth century BC. Context, trade, kalos inscriptions, reception, the fabrication of inscribed painters' names to create a fictitious biography, and the reconstruction of the contents of an Et.